TREATMENT BEHAVIOR OF TUBERCULOSIS PATIENTS IN TABANAN HEALTH CENTER - Sutema, Ida Ayu Manik Partha; Wijayaningrum, I Dewa Ayu Indah; Maharjana, Ida Bagus Nyoman; Ardianta, I Putu Riska (Journal Pharmaceutical Science and Application; Vol 5 No 2 (2023): Journal Pharmaceutical Science and Application, 2023)
Background: Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis. The treatment behavior of tuberculosis patients plays an important role in preventing transmission and recovery of tuberculosis patients, if the treatment behavior of tuberculosis patients is not good it can cause drug resistance, recurrence of tuberculosis disease, even death. Objective: to describe the treatment behavior of tuberculosis patients in the Tabanan Community Health Center area. Methods: This research is a type of quantitative descriptive research conducted in April 2023 at Tabanan Health Center. Measurements were carried out using TPB (Theory of Planned Behavior) questionnaires. Results: This study presents that most respondents had attitudes with enough categories , while the fewer categories amounted and the good category amounted. Conclusion : We found that 57% of respondents suffering from tuberculosis at the Tabanan Health Center had adequate behavior. There is a need for education for tuberculosis patients to prevent and overcome tuberculosis transmission and increase knowledge about tuberculosis infectious diseases either with booklets, leaflets, or animated videos. Keywords : Treatment behavior; Tuberculosis patient; Health center